The Role of Stakeholders in the Implementation of Ecotourism Development Policy in Sindang Panjang Village, Lahat Regency: Peran Pemangku Kepentingan dalam Implementasi Kebijakan Pengembangan Ekowisata di Desa Sindang Panjang, Kabupaten Lahat - Ramadhan, Gilang; Rahmawati, Maulida Putri (Gayaku Publisher, 2024)
This research aims to analyze the role of stakeholders in the implementation of ecotourism development policies in Sindang Panjang Village, Lahat Regency. The method used is qualitative descriptive with a case study approach, allowing the researcher to delve into the dynamics of interactions among government, local communities, business actors, and academics. The results show that stakeholder involvement is still suboptimal, particularly in terms of coordination and collaboration. The local government plays a crucial role in policy formulation and infrastructure provision; however, challenges such as limited budget allocation and external support hinder ecotourism development. The conclusion emphasizes the need for strengthening synergy among stakeholders to achieve sustainable ecotourism development that maximizes benefits for local communities.